KONSTRUKSI SOSIAL PELAYANAN KESEHATAN BERBASIS TAT TWAM ASI - I Wayan Suwirja; Ni Wayan Widhiasthini (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
ABSTRACT Health service standards that can improve service quality and customer satisfaction are health services that are easier, faster, and more practical. To realize excellent service standards, Sanglah General Hospital Denpasar makes "Tat Twam Asi" as a basic belief. This research is a descriptive qualitative research with purposive sampling technique that aims to explore the social construction of health services based on Tat Twam Asi and the contributing factors. The triangulation technique was carried out to confirm the validity of the data in this study. The results of this study found that the concept of Tat Twam Asi was not something new for health servies. It was seen as an important object on behavior in the community especially in the Sanglah General Hospital, however, the implementation was influenced by various factors. The influencing factors are internal factors (individual characteristics and caring to others) and external factors (environment, role models and the role of leaders in reconstruction). It can be concluded that the social construction of health servies on implementing the basic beliefs of Tat Twam Asi has been well constructed but need to be optimized. Therefore, social reconstruction needs to be strengthened to deepen the basic beliefs of Tat Twam Asi. Keywords: Health Services, Social Construction, and Tat Twam Asi.